Body Oxygen Level Test (BOLT) is not associated with exercise performance in highly-trained individuals - Kowalski, Tomasz; Rebis, Kinga; Wilk, Adrian; Klusiewicz, Andrzej; Wiecha, Szczepan; Paleczny, Bartłomiej (Frontiers in Physiology, 2024)
The analysis of chemoreflex and baroreflex sensitivity may contribute to optimizing patient care and athletic performance. Breath-holding tests, such as the Body Oxygen Level Test (BOLT), have gained popularity as a feasible way to evaluate the reflex control over the cardiorespiratory system. According to its proponents, the BOLT score reflects the body's sensitivity to carbon dioxide and homeostasis disturbances, providing feedback on exercise tolerance. However, it has not yet been scientifically validated or linked with exercise performance in highly-trained individuals. Therefore, we investigated the association of BOLT scores with the results of standard performance tests in elite athletes.A group of 49 speedskaters performed BOLT, Wingate Anaerobic Test (WAnT), and cardiopulmonary exercise test (CPET) on a cycle ergometer. Peak power, total work, and power drop were measured during WAnT. Time to exhaustion and maximum oxygen uptake were measured during CPET. Spearman's rank correlation and multiple linear regression were performed to analyze the association of BOLT scores with parameters obtained during the tests, age, somatic indices, and training experience.No significant correlations between BOLT scores and parameters obtained during WAnT and CPET were found, r(47) = -0.172 to 0.013, p = 0.248 to 0.984. The parameters obtained during the tests, age, somatic indices, and training experience were not significant in multiple linear regression (p = 0.38 to 0.85). The preliminary regression model showed an R 2 of 0.08 and RMSE of 9.78 seconds.Our findings did not demonstrate a significant relationship between BOLT scores and exercise performance. Age, somatic indices, and training experience were not significant in our analysis. It is recommended to interpret BOLT concerning exercise performance in highly-trained populations with a great degree of caution.